REVIEW BUKU DALAM KAJIAN LIVING HADIS: Dialektika Teks dan Kontek - Nikmatullah Nikmatullah (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2015)
This article aims at reviewing some literatures dealing with living-hadith study, as well as methods and approaches they use. As can be seen from the literatures, methods and approaches employed do not differ from what are used in the socio-religious studies. This makes it possible for living-hadith study to conduct not only library research, but also field research.